Observations on Social Inclusion and Exclusion, Resource Management, Transformational Politics, Developmental Practices, Gender Relations and Tacit Knowledge - Gurung, Om; Uprety, Laya Prasad; Pandey, Tulsi Ram (Occasional Papers in Sociology and Anthropology, 2010)
DOI: 10.3126/opsa.v11i0.3041 Occasional Papers in Sociology and Anthropology Vol.11 2009 285-291